PREVENTION OF ACCOUNTING FRAUD THROUGH INTERNAL CONTROL SYSTEMS: A LITERATURE REVIEW - Naufiana Al Haq, Zein Maula; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study analyses articles or journals related to internal control's role in preventing accounting fraud. Accountant transparency is a very important aspect in the world of accounting. The method used in this research is a narrative literature review method from several previous studies related to internal control and accounting fraud. The sources used were 13 articles found through Google Scholar using certain keywords. The findings from this study indicate that internal control has a very significant role in preventing accounting fraud practices in various organizational sectors. Implementation of internal control is carried out through the application of adequate authority, responsibility, and supervision.